Artificial Intelligence Integration in Pedagogy and Its Influence on Learning Styles - Adrian Raphael C. Gurion; Dan Emmanuel V. Mateo; Raphael A. Ganiban; Joseph A. Villarama (Blockchain, Artificial Intelligence, and Future Research, 2025)
The rapid integration of Artificial Intelligence (AI) into education has transformed pedagogical strategies and academic approaches of learners. In response to this emerging trend, this study investigated how AI tools are used in teaching at Central Luzon State University Laboratory for Teaching and Learning-University Science High School (CLTL-USHS) and their impacts on students’ learning styles. Employing a phenomenological qualitative research design, hybrid semi-structured interviews were conducted with four teachers and eight Senior High School students over a period of three weeks, with CLSU ethics approval. Findings indicated that teachers frequently use AI tools for plagiarism checking, content generation, lesson planning, and promoting interactive learning, while students perceived AI-supported learning as more personalized, efficient, and engaging, but also recognized challenges such as overdependence, less teacher-student interaction, and concerns about content validity. Through thematic analysis, six main themes with an emphasis of the supportive and challenging function of AI in traditional pedagogy were identified. These findings reflect that while AI tools provide many advantages in forming adaptive learning environments, cautious guidelines should be established to keep educational propriety and human touch in classrooms. The study recommends more teacher training, the development of AI literacy, and ethical guidelines for the responsible use of AI in education.